Itinerário das manifestações culturais da cidade de Pindaré Mirim: aplicação do inventário de varredura e conhecimento - SANTOS, Celso José Brandão (2022)
The present dissertation identified, mapped and inventoried the material and immaterial cultural expressions, as well as their culture makers in Pindaré Mirim city, region that constitutes a historical and cultural formation of great relevance for the territorial configuration of the state of Maranhão. To reach the proposed objectives, the present research made use of an instrument named of Scanning Inventory and Knowledge developed by The National Historical and Artistic Heritage Institute – NHAHI (LONDON, 2000). In this context was made a participant observation and documentary support of stories recorded, memories and identities of a cultural territory of great relevance to the state of Maranhão. As for the Methodology, this research was structured in two moments: a documentary bibliographic, and a field empirical; through which semi-structured interviews were realized and documentation of inventoried goods. Also, it was released iconographic, bibliographic and audiovisual research, consulting federal, state and municipal public agencies, institutions and entities of research, universities, in particular the Noronha Santos Archive of NHAHI. It stands out, that the interviews and application of questionnaires were realized of face-to-face form in Pindaré Mirim city with leaders of cultural groups previously selected and contacted. At the end of the research, it was possible to reach the following results: elaboration of the cultural map of the city, of an electronic portal and an application that gives free access to these cultural expressions of Pindaré Mirim. In front of the results, the research became social, scientific and cultural.